PERKEMBANGAN KEBUGARAN FISIK ORANG DEWASA MUDA DITINJAU DARI JENIS KELAMIN - Junalia Muhammad (Universitas Negeri Medan, 2020)
This research attemps to find out the physical fit developing of man dan woman young adult. Adult age ia a period where nothing changes because the growing factors after growing faster of adoletention age. The physical ability increasing of adult age is no more growing process increasing because getting age, but rather is a results of training and experience. The preeminent difference on move and physical ability between adult man and woman is power. The power difference of both is composition and structure muscles difference because of physical size. The theories in this research are move developing, physical fit, and young adult. The method is cross-sectional method. The researcher collecting data of many various groups with variation age level on same age. The subject in this research are 100 students from FIK Uncen. The data analysis used interactive analysis. The result rate shows the physical fit developing of man young adult with some categories. The categories are excellent category with 10 persons (20%), good category as many 22 persons (44%), sufficient category as many 18 persons (36%), less and much less category is 0 person (0%). On woman young adult category results some categories, there are excellent category as many 6 persons (12%), good category as many 16 persons (32%), less category as many 10 persons (20%), and much less category with 0 person (0%). Thereby, the physical fit developing of man and woman young adult to FIK Uncen students had excellent development. Key words : Fit, young adult, gender